Dual Model of Education in the Republic of Serbia - Lalić, Goran; Trifunović, Dragana (<center>Conference Proceedings Determinants Of Regional Development</center>, 2022)
A lot of work has been done on the development of education, digitalization, new technologies and educational methods in the Republic of Serbia in the last few years. The Republic of Serbia is making significant efforts to adapt its education system to the needs of the economy. In this regard, great efforts are directed towards dual education, which will be presented in this paper. Based on the results of the research, directions of development trends will also be presented.